2008
DOI: 10.1152/ajpheart.00939.2007
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of contractility by Hsp27 and Hic-5 in rat mesenteric small arteries

Abstract: regulation of small artery contractility by vasoconstrictors is important for vascular function, and actin cytoskeleton remodeling is required for contraction. p38 MAPK and tyrosine kinases are implicated in actin polymerization and contraction through heat shock protein 27 (Hsp27) and the cytoskeletal protein paxillin, respectively. We evaluated the roles of downstream targets of p38 MAPK and tyrosine kinases in cytoskeletal reorganization and contraction and whether the two signaling pathways regulate contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
46
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 61 publications
3
46
0
Order By: Relevance
“…We assessed this possibility by treating RMCAs with 5-HT at 10 mm Hg, but an increase, not a decrease, in cofilin phosphorylation was detected. The mechanism of HSP27 inhibition in the myogenic response may also differ; specifically, HSP27 phosphorylation in agonist-and/or stretch-evoked contraction of airway smooth muscle, mesenteric arteries, and rabbit facial vein tissues was shown to be sensitive to inhibition of p38 MAP kinase and/or ROK inhibition rather than PKC (46,101,102). The reason(s) for these varied findings is not known, but an intriguing possibility is that cytoskeletal reorganization in the myogenic response is mediated by a different complement of signaling pathway(s) and membrane adhesion proteins compared with those involved in stretch-, agonist-, or KCl-evoked isometric contraction of VSMCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We assessed this possibility by treating RMCAs with 5-HT at 10 mm Hg, but an increase, not a decrease, in cofilin phosphorylation was detected. The mechanism of HSP27 inhibition in the myogenic response may also differ; specifically, HSP27 phosphorylation in agonist-and/or stretch-evoked contraction of airway smooth muscle, mesenteric arteries, and rabbit facial vein tissues was shown to be sensitive to inhibition of p38 MAP kinase and/or ROK inhibition rather than PKC (46,101,102). The reason(s) for these varied findings is not known, but an intriguing possibility is that cytoskeletal reorganization in the myogenic response is mediated by a different complement of signaling pathway(s) and membrane adhesion proteins compared with those involved in stretch-, agonist-, or KCl-evoked isometric contraction of VSMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Actin dynamics evoked by exposure to vasoconstrictor agonists involves a spatially restricted pool of nonmuscle ␥-and ␤-actin within the cell cortex and at focal adhesions and dense bodies, but not smooth muscle ␣-actin that interacts with tropomyosin and forms the contractile actin filaments within the core of VSMCs (40,41). Roles for additional cytoskeletal and membrane adhesion proteins in smooth muscle contraction have also been identified, including proteins such as talin that serve a structural role, and others that facilitate actin dynamics, such as the actin nucleation initiating factor, N-WASp (neuronal Wiskott-Aldrich Syndrome protein), cofilin, HSP20, HSP27, and VASP (vasodilator-stimulated phosphoprotein) (42)(43)(44)(45)(46)(47).…”
mentioning
confidence: 99%
“…During the last decade, however, it has become increasingly clear that members of this kinase family can participate in signaling pathways activated by of a variety of other membrane receptors, including cytokine and G protein-coupled receptors, to promote cellular functions such as proliferation, growth, inflammation, and contraction (23,26). In particular, it was shown that activation of p38␣ by ␣ 1 -ARs can regulate arterial smooth muscle cell contractility (27) and promote cardiomyocyte sarcomere remodeling during cardiac hypertrophy (10).…”
Section: Discussionmentioning
confidence: 99%
“…The contraction of smooth muscle tissues and cells causes an increase in the pool of filamentous (F) actin and a decrease in the pool of monomeric (globular) (G) actin (12,27,48,65,68,72,84,120,130,143). These transitions in the state of actin have been documented in diverse smooth muscle cell and tissue types using a number of different approaches to estimate monomeric and filamentous pools of actin.…”
Section: A Small Proportion Of Total Actin Undergoes Polymerization Dmentioning
confidence: 99%
“…These transitions in the state of actin have been documented in diverse smooth muscle cell and tissue types using a number of different approaches to estimate monomeric and filamentous pools of actin. These include the use of DNase inhibition assays to measure the amount of globular (G) actin (84), measurements of soluble (G) actin and insoluble (F) actin by cell fractionation (104,120,127,143), fluorescence imaging to visualize G-and F-actin in isolated smooth muscle cells or tissues using G-and F-actin-specific stains (27,48,68,72,130), assessments of the rate of ADP-ATP actin monomer exchange (12), and electron microscopic studies that quantify actin filament density (65). All of these approaches have consistently shown that an increase in F-actin and a decrease in G-actin occurs when smooth muscle cells or tissues are activated by a contractile stimulus.…”
Section: A Small Proportion Of Total Actin Undergoes Polymerization Dmentioning
confidence: 99%